PERAN ORANG TUA TERHADAP KEMAJUAN PRESTASI ATLET SEPATU RODA JOMBANG FREESTYLE CLUB PADA MASA NEW NORMAL - Synthiawati, Novita Nur; Puspitaningsari, Mecca (Dharmas Education Journal (DE_Journal), 2023)
The role of parents in preparing athletes to face changes in the new normal era in Jombang Freestyle Club is an important thing to know in this study, with a descriptive type of research. Data was collected by distributing questionnaires to the parents or guardians of 21 athletes participating in the Jombang Freestyle Club, who were taken using a total sampling technique. The processed descriptive analysis is presented in percentage form. The results of the study revealed that in fact the role of parents in supporting the sports achievement of the Jombang Freestyle Club Roller Skate Athletes was in the category of "very poor" with a percentage of 0%, "poor" with a percentage of 33%, "enough" with a percentage of 33%, "good" with a percentage of 29%, and "very good" represents 5%. Referring to the average score, which is 100, the role of parents in supporting the sports achievements of the Jombang Freestyle Club roller skate athletes is in the sufficient category.